Comparison of short-wavelength blue-light autofluorescence and conventional blue-light autofluorescence in geographic atrophy. Issue 5 (5th June 2018) - Borrelli, Enrico; Nittala, Muneeswar Gupta; Abdelfattah, Nizar Saleh; Lei, Jianqin; Hariri, Amir H; Shi, Yue; Fan, Wenying; Cozzi, Mariano; Sarao, Valentina; Lanzetta, Paolo; Staurenghi, Giovanni; Sadda, SriniVas R
Abstract : Background/aims: To systematically compare the intermodality and inter-reader agreement for two blue-light confocal fundus autofluorescence (FAF) systems. Methods: Thirty eyes (21 patients) with a diagnosis of geographic atrophy (GA) were enrolled. Eyes were imaged using two confocal blue-light FAF devices: (1) Spectralis device with a 488 nm excitation wavelength (488-FAF); (2) EIDON device with 450 nm excitation wavelength and the capability for 'colour' FAF imaging including both the individual red and green components of the emission spectrum. Furthermore, a third imaging modality (450-RF image) isolating and highlighting the red emission fluorescence component (REFC) was obtained and graded. Each image was graded by two readers to assess inter-reader variability and a single image for each modality was used to assess the intermodality variability. Results: The 95% coefficient of repeatability (1.35 mm 2 for the 488-FAF-based grading, 8.13 mm 2 for the 450-FAF-based grading and 1.08 mm 2 for the 450-RF-based grading), the coefficient of variation (1.11 for 488-FAF, 2.05 for 450-FAF, 0.92 for 450-RF) and the intraclass correlation coefficient (0.994 for 488-FAF, 0.711 for 450-FAF, 0.997 for 450-RF) indicated that 450-FAF-based and 450-RF-based grading have the lowest and highest inter-reader agreements, respectively. The GA area was larger for 488-FAF images (median (IQR) 2.1 mm 2  (0.8–6.4 mm 2 )) than for 450-FAF images (median (IQR) 1.0 mm 2  (0.3–4.3 mm 2 ); p<0.0001). There was no significant difference in lesion area measurement between 488-FAF-based and 450-RF-based grading (median (IQR) 2.6 mm 2  (0.8–6.8 mm 2 ); p=1.0). Conclusion: The isolation of the REFC from the 450-FAF images allowed for a reproducible quantification of GA. This assessment had good comparability with that obtained with 488-FAF images.